Kepatuhan Perawat Dalam Menyimpan Obat High Alert Di Unit Kritis Rumah Sakit Advent Bandungs Rumah sakit Advent Bandung - Ambarwati ambarwati; Mori Agustina Br Perangin-angin (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
The critical unit is a treatmenta room for patients with severe conditions that require close observation and advanced treatment. Due to severe conditions, patients are given therapy and types of drugs that require special attention or are often called high alert drugs, either in providing, giving or storing. The administration of drug in an inappropriate manner can cause a reaction that is dangerous to the patient and improper storage can also harm the patient materially.This study aims to determinethe compliance of nurse in the high alert drug storage processin the Critical Care Room in Bandung Adventist Hospital. The storage process includes labeling high alert drugs including high concentration electrolytes,cytostatic drugs,similar speech drugs ( NORUM AND LASA ),narcotics,insulin,antiarythmia,inotropics, and anticoagulants. The method used in this research is descriptive, namely through the data obtained fron the compliance of nurse who are in the critical care roomin Bandung Adventist Hospital regarding the storage process and high alert drug services. The results showed that the compliance of nurses who were in the critical care room who was the most obedient in storing high alert drugs was the NICU-PICU (Neonatal Intensive Care Unit - Pediatric Intensive Care Unit) room with an adherence rate of 86,01%. While the space that is lacking in compliance with high alert drug storage is the HCU-ICCU ( High Care Unit- Intensive Caronary Care Unit) room of rate 77,56% . This shows that the level of compliance thatis owned is still below the standard qualityindicator, which is 100%. So,it requires commitment by the nursesto better complywith the high alert drug storageand service protocols.